Comparison of resistance to third-generation cephalosporins in Shigella between Europe-America and Asia-Africa from 1998 to 2012. (2nd January 2015) - GU, B.; ZHOU, M.; KE, X.; PAN, S.; CAO, Y.; HUANG, Y.; ZHUANG, L.; LIU, G.; TONG, M.
SUMMARY: We conducted a systematic review to compare resistance to third-generation cephalosporins (TGCs) in Shigella strains between Europe-America and Asia-Africa from 1998 to 2012 based on a literature search of computerized databases. In Asia-Africa, the prevalence of resistance of total and different subtypes to ceftriaxone, cefotaxime and ceftazidime increased markedly, with a total prevalence of resistance up to 14·2% [95% confidence interval (CI) 3·9–29·4], 22·6% (95% CI 4·8–48·6) and 6·2% (95% CI 3·8–9·1) during 2010–2012, respectively. By contrast, resistance rates to these TGCs in Europe-America remained relatively low – less than 1·0% during the 15 years. A noticeable finding was that certain countries both in Europe-America and Asia-Africa, had a rapid rising trend in the prevalence of resistance of S. sonnei, which even outnumbered S. flexneri in some periods. Moreover, comparison between countries showed that currently the most serious problem concerning resistance to these TGCs appeared in Vietnam, especially for ceftriaxone, China, especially for cefotaxime and Iran, especially for ceftazidime. These data suggest that monitoring of the drug resistance of Shigella strains should be strengthened and that rational use of antibiotics is required.